2020
DOI: 10.1111/ejn.14722
|View full text |Cite
|
Sign up to set email alerts
|

The onset speed of hyperglycemia is important to the development of neuropathic hyperalgesia in streptozotocin‐induced diabetic rats

Abstract: Diabetic neuropathic hyperalgesia is one of the most common diabetes complications. The physiopathological mechanism of hyperalgesia and the reason by which this condition affects only part of the diabetic patients still unclear. We tested whether an adaptation of primary afferent neurons to hyperglycemia could prevent the development of hyperalgesia. Hyperglycemia was induced in male Wistar rats by a daily administration of a low dose of streptozotocin (STZ), during five consecutive days. Glycemia and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
4
1
4
Order By: Relevance
“…Furthermore, our study revealed amelioration in the fasting blood glucose levels of all the treated diabetic groups. In contrast to our findings with respect to Oxalis corniculata, it was demonstrated that a single daily oral administration of an aqueous extract of Oxalis corniculata (100 mg/kg body weight) caused a significant reduction in the blood glucose in Alloxan-induced diabetic mice when treated for a period of ten days (do Prado et al, 2020). The results observed in our study are based on a different dose and feeding duration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our study revealed amelioration in the fasting blood glucose levels of all the treated diabetic groups. In contrast to our findings with respect to Oxalis corniculata, it was demonstrated that a single daily oral administration of an aqueous extract of Oxalis corniculata (100 mg/kg body weight) caused a significant reduction in the blood glucose in Alloxan-induced diabetic mice when treated for a period of ten days (do Prado et al, 2020). The results observed in our study are based on a different dose and feeding duration.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, there were no studies to compare the results obtained from treating diabetic animals with Pteropyrum scoparium or the mixture of two plants. Long term of untreated hyperglycemia in diabetes is as- Al-Qalhati, Waly, Al-Subhi, Al-Attabi sociated with oxidative stress generating from glucose autoxidation, protein glycation and glycoxidation leading to tissue injury and damage (do Prado et al, 2020). Induction of STZ generates H2O2 and increased the production of free radicals in vitro as well as in vivo increasing the oxidative stress level (Balaji et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…DM is known to damage various regions of the brain, including the hippocampus, cortex, and cerebellum, due to the excessive oxidative stress ( do Prado et al, 2020 ; Tong & Cheng, 2005 ). Melatonin is shown to protect the brain from DM-stimulated glial cell activation and ROS in STZ-induced diabetic rats ( Barber et al, 2000 , Antonetti, Gardner, and Penn State Retina Res, 2000; Renno, Alkhalaf, Afsari, Abd-El-Basset, & Mousa, 2008 ) ( La Morgia et al, 2010 ; Galley et al, 2017 ).…”
Section: Effect Of Melatonin Treatment On Diabetic Neuropathy In Expe...mentioning
confidence: 99%
“…It has been shown that slow increase of glycemia produced by several daily small doses of STZ allows adaptation to nociceptive stimuli producing less pain; in contrast, sudden high hyperglycemia produced by higher STZ doses reduced such adaptation. 39 Such adaptation is like the phenomenon named preconditioning. In fact, animals that are separated from their original cages are stressed.…”
Section: Glucose and Weightmentioning
confidence: 99%
“…41 Decreased adaptation during hyperglycemia has been attributed to mitochondrial dysfunction. 39 Moreover, STZ has direct (effects on lymphocytes producing lymphopenia) and indirect (hyperglycemia) immunosuppressive activity. 42 Therefore, changes of heme, Hb, oxyHb, and p450 in the first two weeks after STZ could be due to lack of adaptation and immunosuppression.…”
Section: Glucose and Weightmentioning
confidence: 99%